Application of Religious Values in Forming Prosocial Attitudes of Grade VIII Students at SMPN 14 Baubau - Mulnur, Shelomita; Yahya, Safaruddin; Madi, Madi (Journal of English Language and Education, 2025)
This study explores the application of religious values in shaping prosocial attitudes of eighth grade students at SMP Negeri 14 Baubau. Prosocial attitudes, such as helping and sharing, are crucial for character development. Using a descriptive qualitative approach, data were collected through observation, interviews with religious teachers and students, and analysis of religious activity documents. This study aims to determine how religious values are applied in shaping prosocial attitudes of students at SMP Negeri 14 Baubau. The results of this study are that the prosocial attitudes of students at SMP Negeri 14 Baubau are still relatively weak/low because some students are less sensitive to the condition of their friends, the religious values applied to students at SMP 14 Baubau are the implementation of Islamic holidays, holding prayers together every midday prayer, and extracurricular activities, the method of applying religious values in shaping prosocial attitudes of students at SMP 14 Baubau is through habituation, role models, story or story methods, methods of educating through discipline, advice methods, and methods of religious-based extracurricular activities.